Tanggung Jawab Orang Tua dalam Perlindungan Anak di Era Digital: Perspektif Hukum Islam dan Hukum Nasional - Muna, Khoirul; Widiyanto, Hari; Abqori, Najih (Kartika: Jurnal Studi Keislaman, 2026)
The digital era has had a significant impact on family life, including the way parents interact with their children. While open access to information offers positive opportunities for children's learning, it also raises various issues, such as the potential for technology misuse, exposure to inappropriate content, and a decline in moral values. In the context of Islamic family law in Indonesia, parents' obligations extend beyond meeting material needs to safeguarding children's moral and spiritual well-being. This research focuses on analyzing the role of parents in providing child protection in the digital era, drawing on Islamic and national legal perspectives. The method used is a literature review using a descriptive-qualitative approach and deductive analysis. The research findings confirm that parental responsibility aligns with the five main objectives of the maqāṣid al-syarī‘ah, namely safeguarding religion (ḥifẓ al-dīn), safeguarding the soul (ḥifẓ al-nafs), safeguarding reason (ḥifẓ al-‘aql), safeguarding honor (ḥifẓ al-‘irḍ), and safeguarding property (ḥifẓ al-māl). These values are also in line with the provisions of Law Number 35 of 2014 concerning Child Protection. Therefore, parents are required to be actively involved in the process of educating, supervising, and protecting their children so that they can develop into a generation that is faithful, has good morals, and is capable of utilizing technology.